2019
DOI: 10.1182/blood-2018-10-879247
|View full text |Cite
|
Sign up to set email alerts
|

Luspatercept improves hemoglobin levels and blood transfusion requirements in a study of patients with β-thalassemia

Abstract: K E Y P O I N T S l A high percentage of patients with b-thalassemia had improvement in hemoglobin or transfusion burden after receiving luspatercept. l Findings support a randomized clinical trial to assess the efficacy and safety of luspatercept for treatment of b-thalassemia. b-thalassemia is a hereditary disorder with limited approved treatment options; patients experience anemia and its complications, including iron overload. The study aim was to determine whether luspatercept could improve anemia and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
102
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(108 citation statements)
references
References 19 publications
4
102
2
Order By: Relevance
“…The use of erythropoiesis‐stimulating agents, such as erytropoietin, in beta‐thalassemia is not supported by controlled clinical trials (Fibach & Rachmilewitz, ). Recently, an open‐label, nonrandomized, uncontrolled study demonstrated an improvement in hemoglobin and transfusion burden in patients with beta‐thalassemia after the use of luspatercept (Piga et al , ). Therefore, iron chelation therapy (ICT) currently remains the main treatment for iron overload and for its complications in patients with thalassemia.…”
Section: Main Patients’ Characteristicsmentioning
confidence: 99%
“…The use of erythropoiesis‐stimulating agents, such as erytropoietin, in beta‐thalassemia is not supported by controlled clinical trials (Fibach & Rachmilewitz, ). Recently, an open‐label, nonrandomized, uncontrolled study demonstrated an improvement in hemoglobin and transfusion burden in patients with beta‐thalassemia after the use of luspatercept (Piga et al , ). Therefore, iron chelation therapy (ICT) currently remains the main treatment for iron overload and for its complications in patients with thalassemia.…”
Section: Main Patients’ Characteristicsmentioning
confidence: 99%
“…In conclusion, a high prevalence of decreased β‐cell insulin secretion was demonstrated among children and adolescents with Hb H disease, and this insulin secretory defect is likely to be related to the severity of anemia, independent of the type of Hb H disease. Whether or not increasing the functional Hb levels by blood transfusion or novel therapy on enhanced erythroid maturation will ameliorate insulin secretory defect has yet to be established. Further study is needed to prevent long‐term complications related to abnormal glucose metabolism in patients with Hb H disease.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, many causes of anemia are unresponsive to exogenous Epo. Recently, TGFβ superfamily activin receptor (Acvr2a/b) ligand traps have shown activity treating chronic Epo-unresponsive anemia in myelodysplastic syndrome (MDS) and beta-thalassemia and are thought to promote erythroid maturation after Epo signaling [22][23][24][25][26] . However, the molecular regulators of the Epo-unresponsive erythroid compartment are not well defined.…”
Section: Discussionmentioning
confidence: 99%